Implementation of TQM at Palangka Raya State Vocational School: Improving the Role of Teachers and Education Personnel - Sadrakh Balinga; Retty Marinda; Aslamiah Aslamiah; Celia Cinantya (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2026)
The implementation of Total Quality Management (TQM) in State Vocational Schools (SMK) in Palangka Raya aims to enhance the quality of education sustainably through the management of learning, teacher and staff involvement, and curriculum development. This study employs a qualitative approach with a case study method, utilizing in-depth interviews, observations, and document analysis as data collection techniques. TQM focuses on student and parent satisfaction, as well as improving the quality of graduates to be more competitive in the job market.The results of TQM implementation indicate significant improvements in education quality, including increased satisfaction among students and parents. However, challenges such as limited human resources, budget constraints, and management's lack of sustained commitment persist. To address these challenges, State Vocational Schools have conducted teacher training, established collaborations with industries, and implemented transparent evaluation systems. By instilling a culture of quality throughout all school elements, it is hoped that State Vocational Schools can continuously improve educational quality and produce graduates who excel in the workforce.